Market reactions to mandated interest capitalization* - HUGHES, JOHN S.; RICKS, WILLIAM E. (Contemporary Accounting Research, 1986)
Abstract. Following a five year moratorium on adoption of interest capitalization by the SEC, the Financial Accounting Standards Board issued SFAS No. 34 mandating that firms previously writing off interest charges related to the construction of assets change to capitalizing those charges. The purpose of this study is to analyze the impact of this change in terms of the security market's reactions both to policy announcements leading up to the promulgation of SFAS No. 34, and to earnings announcements following implementation by affected companies. Significant average market reactions are indicated for two of ten policy announcements before the effects of firm size are considered; however, significance disappears when those effects are removed from excess returns. Although a bias is detected in the forecasts of analysts consistent with less than full revision to include the earnings impact, there is little evidence of market reactions to announcements of those earnings. Résumé. Après un moratoire de cinq ans sur l'adoption de la capitalisation de l'intérêt par la S.E.C., le Financial Accounting Standards Board a émis le bulletin numéro 34 qui demande aux entreprises qui passaient aux dépenses les charges d'intérêts reliées à la construction d'actifs, de les capitaliser. L'objectif de cette étude, est d'analyser l'impact de ce changement (en termes des réactions du marché des valeurs) aux annonces de politiques qui ont conduit à la promulgation du bulletin 34 et aux annonces de bénéfices qui ont suivi l'implantation pour les compagnies touchées. Les réactions du marché en moyenne sont significatives pour deux des dix annonces de politiques, avant de prendre en considération les effets de l'ampleur de la firme; cependant, ce n'est plus significatif lorsque ces effets sont retranchés des rendements excédentaires. Quoiqu'un biais soit détecté dans les prévisions des analystes, en accord avec une révision moins que complète pour inclure l'impact des bénéfices, il y a peu d'évidence des réactions du marché aux annonces de ces bénéfices.